Efektifitas Penyuluhan Kesehatan Menggunakan Media Video Terhadap Pengetahuan Remaja Putri Tentang SADARI di SMA Negeri 1 Karang Intan - Misna Tazkiah; Ince Fitriah (Jurnal Kesehatan Indonesia, 2020)
The incidence of breast cancer from year to year is increasing. This is influenced by the low knowledge of young women regarding BSE examination. Efforts to increase the knowledge of young women one of them through self-awareness counseling, conducting breast self-examination as early as possible then the life expectancy of 80-90% higher recovery. This study aims to determine the effectiveness of "BSE" health education with a video on the knowledge of young women in Karang Intan 1 High School. This research is a quantitative study using a pre experimental design with one group pre post test. Samples were 20 Social Sciences class 12 students at SMA 1 Karan Intan of 20 people. The collection instrument is a questionnaire and intervention using video media. Data analysis using paired T-test. The results of the study showed the average value of knowledge before being provided with counseling with video media was 47.75 and the average value of knowledge after being provided with health counseling with video media was 78.00. The analysis showed that there were differences in the knowledge of young women about BSE between before and after health education using video media (p = 0,000). It is recommended to further increase the use of video media as a health counseling media